Irinotecan-Induced Gastrointestinal Dysfunction Is Associated with Enteric Neuropathy, but Increased Numbers of Cholinergic Myenteric Neurons - McQuade, Rachel M.; Stojanovska, Vanesa; Donald, Elizabeth L.; Rahman, Ahmed A.; Campelj, Dean G.; Abalo, Raquel; Rybalka, Emma; Bornstein, Joel C.; Nurgali, Kulmira (Frontiers in Physiology, 2017)
Gastrointestinal dysfunction is a common side-effect of chemotherapy leading to dose reductions and treatment delays. These side-effects may persist up to 10 years post-treatment. A topoisomerase I inhibitor, irinotecan (IRI), commonly used for the treatment of colorectal cancer, is associated with severe acute and delayed-onset diarrhoea. The long-term effects of IRI may be due to damage to enteric neurons innervating the gastrointestinal tract and controlling its functions. Balb/c mice received intraperitoneal injections of IRI (30 mg/kg-1) 3 times a week for 14 days, sham-treated mice received sterile water (vehicle) injections. In vivo analysis of gastrointestinal transit via serial x-ray imaging, faecal water content, assessment of gross morphological damage and immunohistochemical analysis of myenteric neurons were performed at 3, 7 and 14 days following the first injection and at 7 days post-treatment. Ex vivo colonic motility was analysed at 14 days following the first injection and 7 days post-treatment. Mucosal damage and inflammation were found following both short and long-term treatment with IRI. IRI-induced neuronal loss and increases in the number and proportion of ChAT-IR neurons and the density of VAChT-IR fibres were associated with changes in colonic motility, gastrointestinal transit and faecal water content. These changes persisted in post-treatment mice. Taken together this work has demonstrated for the first time that IRI-induced inflammation, neuronal loss and altered cholinergic expression is associated with the development of IRI-induced long-term gastrointestinal dysfunction and diarrhoea.